The effect of one-step or two-step MTA plug and tooth apical width on coronal leakage in open apex teeth - Khalilak, Zohreh; Vali, Tabasom; Danesh, Farzad; Vatanpour, Mehdi (Iranian Endodontic Journal, 2011)
Introduction: Mineral trioxide aggregate (MTA) has been suggested as an effective material for apical barrier, forming an effective seal against bacterial leakage in teeth with open apices. MTA needs moisture for setting; which can come from the apical region or a moist cotton pellet. This study was intended to compare bacterial leakage in one- and two-step MTA apical barrier technique in open apices with different diameters. Materials and Methods: The root canals of 52 extracted human maxillary incisors were prepared and open apices in two different diameters of 1 and 1.4 mm were created. The samples put in experimental groups randomly. A 4-mm thickness of MTA was placed as apical barrier for both one- and two-step methods. In one-step groups (1.4 mm diameter; n=12 and 1 mm diameter; n=12), the samples were obturated immediately after placing MTA plug. For two-step groups (1.4 mm diameter; n=12 and 1 mm diameter; n=12), a moist cotton pellet was placed over the MTA plug for 3 days before root canal obturation. Four samples served as positive/negative control groups. After one week, microleakage was evaluated using bacterial penetration technique and results were statistically analyzed utilizing SPSS software and Chi-square test. Results: In one-step technique 13 and in two-step technique 12 samples showed bacterial leakage. There was no statistically significant differences between two techniques (Chi square, P=1). The difference between the results related to 1 and 1.4 mm apical foramens was also not significant (P=1). Also 12 and 13 samples showed bacterial contamination in teeth with 1 mm and 1.4 mm apical foramens, respectively (P=1). Conclusion: It seems that leakage of MTA apical plug using one- and two-step technique is comparable; however, in vivo investigations are highly recommended for more accurate results.